Persiapan dan Posisi Ibu dalam Persalinan - Hasriani Saleng; Dwi Ghita; Nurqalbi Sampara (PT FORMOSA CENDEKIA GLOBAL, 2022)
Childbirth is a vulnerable period for a woman who experiences pregnancy in her life cycle. The labor process is prone to experiencing various complications, one of the things that is naturally felt by maternity is the comfort and well-being of her body in dealing with labor contractions so that a comfortable position is needed for the mother to face her delivery without complications. Mother's preparation in labor is by choosing a position in labor. There are several positions in the labor process, namely left tilt, right side lying, semi sitting/semi fowler, lithotomy, squatting, knee chest. The purpose of this service is to provide education for mothers in dealing with childbirth, it requires preparation and knowledge related to the ideal position in childbirth that is safe, comfortable and healthy for mothers and their babies. The method used in this counseling is a demonstration of the delivery position. Based on the results of the activity, 15 pregnant women in the work area of ​​the Pattingalloang Public Health Center participated in the counseling activities.